A Simple Ultrasound Examination as Diagnostic Tool for Malignant Ovarian Tumor - Wigin, Christin; Andrijono, Andrijono (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To know the diagnostic value of simple ultrasound examination to detect malignant ovarian tumor. Method: This study used cross-sectional design in gynecology outpatientclinic at Dr. Cipto Mangunkusumo Hospital. We recruited the patients with ovarian tumor undergoing surgery between March and July 2015. Samples were taken using consecutive sampling. Analysis was done using Chi-square test and logistic regression to find the relationship between ultrasound morphologic patterns with histopathologic findings, where the significant relationship was p value less than 0.05. Furthermore, a model derived from logistic regression was made to calculate the probability having ovarian malignancy. Result: There were 80 subjects which 58 subjects (72.5%) had benign tumor and 22 subjects (27.5%) had malignant tumor. Ultrasound examination result using  2 morphologic patterns gave malignant result in 53.8% subjects with the sensitivity of 100%, specificity of 82.8%, positive predictive value of 68.8%, and negative predictive value of 100%. The most important patterns were irregular internal cyst wall, multilocular, presence of papillary projection, and presence of solid component. The probability of subject having ovarian malignancy with  3 morphologic patterns was more than 88.9%. Conclusion: Simple ultrasound examination can be used to detect malignant ovarian tumor. [Indones J Obstet Gynecol 2016; 4-4: 222-226] Keywords: diagnostic, histopathology, morphology pattern; ovarian tumor; ultrasonography